Feasibility of biological aerated filters (BAFs) for treating landfill leachate - Stephenson, Tom; Pollard, Simon J. T.; Cartmell, Elise (Cranfield University, 2004)
Ammonia can be removed from landfill leachate through aerobic biological processes. The biological aerated filter (BAF) combines biological treatment and subsequent biomass separation in one reactor providing a small footprint alternative to conventional systems. Leachate from an operational landfill was found to be aerobically treatable using the OECD recommended Modified Zahn- Wellens test. This leachate was used as feed to a pilot-scale BAF at influent COD and ammoniacal-nitrogen concentrations of 765 mg/l and 568 mg/ l respectively. During an initial period of stable operation without pH control, 33 % of influent ammonia was removed. The reactor pH was 9.2 with little conversion to total oxidized nitrogen (<45 mg/l). Therefore this removal was accounted for primarily by air stripping. In a second period of stable operation, the reactor pH was reduced to pH 7.2 by addition of hydrochloric acid. Ammonia removal was increased to 97 % with a concomitant increase in effluent nitrite concentration to an average of 524 mg/l. Biological aerated filters can therefore be used to nitrify landfill leachates.